Memory development course - Conversa-phone Institute ([Farmingville, NY] : Conversa-phone Institute)
This course will cover many important phases of memory development, such as how to remember names and faces, telephone numbers, dates, etc. But more important, it will build the groundwork to remember anything we really want to remember
H 35097
Keywords: Short-term memory; Memory